Rancang Bangun Aplikasi Layanan Informasi dan Pemesanan Tiket pada Objek Wisata Situ Bagendit Berbasis Mobile - Septiana, Yosep; Tresnawati, Dewi; Nurohmah, Novita Fitri; Ikhwana, Andri (Jurnal Algoritma, 2023)
The development of technology is a tool that is much needed by tourism to make it easier to obtain information and can also help, simplify and speed up tourist attraction managers in managing data on tourist visits. This information aims to increase tourism profits. Situ Bagendit is a tourist attraction in Bagendit Village, District. Banyuresmi, Kab. Garut. Situ Bagendit is a tourist spot that is of interest to many visitors. Based on the results of interviews with the management of Situ Bagendit and seeing that there are problems with information services where the presentation of information about this tourist attraction is still minimal, whereas after revitalizing this tourist attraction it will become an international scale tourist attraction and also ticket reservations are recorded manually, namely the door guard or the person guarding it. in terms of serving visitors to buy and make payments, they still use paper. The aim of this research is to create an application regarding information services and ticket reservations at these tourist attractions as an effort to make it easier for visiting tourists to find information in advance and order tickets online, tourists no longer need to queue to order tickets. Similar literature studies, field studies with observations and interviews, and literature studies were used to collect data. The methodology used is the Unified Software Development Process, then uses the Flutter framework and Unified Modeling Language modeling and applies the Mobile concept. The results of the research carried out are in the form of a mobile-based application for information services and ticket reservations at the Situ Bagendit tourist attraction so that it can convey information about the tourist attraction and help make it easier for tourists to order tickets online so that those who will visit can make reservations in advance and without delay. have to queue first.